Three new pancreatic cancer susceptibility signals identified on chromosomes 1q32.1, 5p15.33 and 8q24.21 - Zhang, Mingfeng; Wang, Zhaoming; Obazee, Ofure; Jia, Jinping; Childs, Erica J; Hoskins, Jason; Figlioli, Gisella; Mocci, Evelina; Collins, Irene; Chung, Charles C; Hautman, Christopher; Arslan, Alan A; et al. (Oncotarget, 2016)
Genome-wide association studies (GWAS) have identified common pancreatic cancer susceptibility variants at 13 chromosomal loci in individuals of European descent. To identify new susceptibility variants, we performed imputation based on 1000 Genomes (1000G) Project data and association analysis using 5,107 case and 8,845 control subjects from 27 cohort and case-control studies that participated in the PanScan I-III GWAS. This analysis, in combination with a two-staged replication in an additional 6,076 case and 7,555 control subjects from the PANcreatic Disease ReseArch (PANDoRA) and Pancreatic Cancer Case-Control (PanC4) Consortia uncovered 3 new pancreatic cancer risk signals marked by single nucleotide polymorphisms (SNPs) rs2816938 at chromosome 1q32.1 (per allele odds ratio (OR) = 1.20, P = 4.88x10 -15), rs10094872 at 8q24.21 (OR = 1.15, P = 3.22x10 -9) and rs35226131 at 5p15.33 (OR = 0.71, P = 1.70x10 -8). These SNPs represent independent risk variants at previously identified pancreatic cancer risk loci on chr1q32.1 ( NR5A2), chr8q24.21 ( MYC) and chr5p15.33 ( CLPTM1L- TERT) as per analyses conditioned on previously reported susceptibility variants. We assessed expression of candidate genes at the three risk loci in histologically normal ( n = 10) and tumor ( n = 8) derived pancreatic tissue samples and observed a marked reduction of NR5A2 expression (chr1q32.1) in the tumors (fold change -7.6, P = 5.7x10 -8). This finding was validated in a second set of paired ( n = 20) histologically normal and tumor derived pancreatic tissue samples (average fold change for three NR5A2 isoforms -31.3 to -95.7, P = 7.5x10 -4-2.0x10 -3). Our study has identified new susceptibility variants independently conferring pancreatic cancer risk that merit functional follow-up to identify target genes and explain the underlying biology.
Keywords: Genotype; imputation; Genome-Wide Association Study; NR5A2; jednonukleotidový polymorfismus; Datasets as Topic; lidské chromozomy, pár 8; Pancreatic Neoplasms; GWAS; lidé; Polymorphism, Single Nucleotide; genotyp; nádory slinivky břišní; genetická predispozice k nemoci; fine-mapping; Genetic Predisposition to Disease; Chromosomes, Human, Pair 1; lidské chromozomy, pár 1; pancreatic cancer; datové soubory jako téma; celogenomová asociační studie; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 8; lidské chromozomy, pár 5; Humans